الحصانة القضائية للموظف الدبلوماسي في القانون الدولي اتفاقية فيينا 1961م، واتفاقية روما 2005م - فرحات، مصطفى العماري إعمارة (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
Judicial diplomatic immunity is considered to be of a high significance as it provides ‎an atmosphere of freedom that enables the diplomatic official to perform the tasks ‎entrusted to him without interference of the hosting country, whereas most ‎countries resorted to exploiting it, by giving serious crime perpetrators such as ‎crimes against humanity, to be exclusive to the users of diplomatic immunity. This ‎study also aims at identifying the role of the judicial immunity of the diplomatic ‎official in the international Law through the identification of the essential nature of ‎the judicial diplomatic immunity and basics thereof and notions to which it is ‎connected and also the theories pertaining to the immunities and types thereof, and ‎then a statement of the scope of such immunity in terms of place, time and persons ‎and then statement of the diplomatic subjection to the competence of the ‎International Criminal Court. Also, Vienna Law in this concern shall be studied. This ‎study has also focused on the problem that theories are based on granting judicial ‎immunity and whereas the diplomatic function is determined by a certain term, ‎hence, the judicial immunity revolves in terms of existence and non-existence with ‎such function, the matter that necessitates the knowledge of the function time, the ‎persons involved in such immunity and the spatial scope of the validity of immunity ‎and the possibility of subjection of diplomat to the International Criminal Court. ‎Thus, research followed the descriptive method and historical method with the ‎discussion of the theoretical framework of the study subject in terms of its inclusion ‎of the understanding of its dimensions from al the fields, which shall include the ‎judicial immunity and its basics and types. Hence, the study reached several results, ‎the most important is the acquaintance with the tasks of Rome Convention and ‎Vienna Convention with the International Criminal Court. The results of the study ‎have also clarified that the machinery of arresting the diplomat is marked by ‎complication of measures as long as the envoy country has not withdrawn immunity ‎from him and to which he clung. The study recommended the reformulation of laws ‎in force in the Criminal Court and give them sufficient powers to fully undertake its ‎tasks and that the International Criminal Court is characterized by neutrality for all ‎the countries of the world.‎‎